2020
DOI: 10.3390/diagnostics10060428
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Endotoxemia, Feeding Studies and the Use of the Limulus Amebocyte (LAL) Assay; Is It Fit for Purpose?

Abstract: The Limulus amebocyte assay (LAL) is increasingly used to quantify metabolic endotoxemia (ME), particularly in feeding studies. However, the assay was not intended to assess plasma at levels typically seen in ME. We aimed to optimize and validate the LAL assay under a range of pre-treatment conditions against the well-established lipopolysaccharide binding protein assay (LBP). Fifteen healthy overweight and obese males aged 28.8 ± 9.1years provided plasma. The LAL assay employed a range of pre-treatments; 70 °… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In addition, the half-life of LPS is very short, as it is rapidly sequestered by LBP ( 133 ). To overcome all of these limitations (which is challenging), one could use several assays togethers with the LAL assay, such as the LBP assay and the endotoxin activity assay (EAA) ( 134 ). Thus, care should be taken when attributing any pathology associated with a positive LAL test result to the presence of LPS (cause-effect-relationship).…”
Section: Limitationsmentioning
confidence: 99%
“…In addition, the half-life of LPS is very short, as it is rapidly sequestered by LBP ( 133 ). To overcome all of these limitations (which is challenging), one could use several assays togethers with the LAL assay, such as the LBP assay and the endotoxin activity assay (EAA) ( 134 ). Thus, care should be taken when attributing any pathology associated with a positive LAL test result to the presence of LPS (cause-effect-relationship).…”
Section: Limitationsmentioning
confidence: 99%
“…At present, LBP has been suggested as one of the preferred, surrogate markers of endotoxemia but is likely not indicated/appropriate in acute instances (i.e., minutes/hours) [139]. Furthermore, if the LAL assay is used, researchers should calculate and report correlations with other metrics like LBP or another alternative method of analysis as a quality measure [139].…”
Section: Lps Detection and Defining Serotype Specificitymentioning
confidence: 99%
“…For LPS detection, the LAL reactivity assay is widely used, though is susceptible to capturing several nonspecific activators and inhibitors in circulation making accurate quantification of LPS challenging, particularly at lower concentrations [137,138]. For this reason, the LAL assay has recently been regarded as inappropriate for metabolic endotoxemia studies [139]. Moreover, detecting differences in LPS structure with the LAL test is not possible.…”
Section: Lps Detection and Defining Serotype Specificitymentioning
confidence: 99%
“…In this study, the effects of HK L-137 on obesity and associated metabolic markers were observed in the early phase, while a trend toward a decrease in plasma LBP levels caused by HK L-137 was seen in the late phase. We consider that the inhibitory effects of HK L-137 on increases in LPS permeability might occur in the early phase of diet-induced obesity, but we could not detect them timely by measuring plasma LBP levels because of time-lag bias between LPS translocation and LBP synthesis [29]. Further experiments are needed.…”
Section: Discussionmentioning
confidence: 98%